Conflict and food security in Sudan: Policy insights and recommendations - Kirui, Oliver K.; Siddig, Khalid; Ahmed, Mosab O. M.; Abushama, Hala; Dorosh, Paul A.; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2024)
The conflict in Sudan erupted on April 15, 2023. Originating from competition over resources and political power, it emerged as direct warfare between the Sudanese Armed Forces and the Rapid Support Forces. It has escalated into a crisis with profound impacts on the nation’s socio-economic fabric. More specifically, the conflict has led to a severe humanitarian crisis, disrupted agrifood systems across the country, restricted economic activity, and curtailed the livelihoods of millions. The conflict continues to impede access to essential services and markets, resulting in significant scarcity of life-saving goods and services. As of March 2024, 14,790 Sudanese have been killed (Figure 1), and 8.4 million have been displaced, of which1.7 million have sought refuge in other countries.